Highly pressurized helium nanobubbles promote stacking-fault-mediated deformation in FeNiCoCr high-entropy alloy. (15th May 2021) - Lin, W.T.; Chen, D.; Dang, C.Q.; Yu, P.J.; Wang, G.; Lin, J.H.; Meng, F.L.; Yang, T.; Zhao, Y.L.; Liu, S.F.; Du, J.P.; Yeli, G.M.; et al.
Abstract: Tailoring nanoscale defect structures for desirable deformation behaviors is crucial to designing and optimizing the mechanical properties of alloys. Distinguishing from the predominant toughening mechanisms (e.g., mechanical twinning and deformation-induced phase transformation), here we report an unusual stacking-fault-mediated deformation in equiatomic FeNiCoCr high-entropy alloy (HEA) by controllably introducing helium nanobubbles with high pressures of ~2.5-4.7 gigapascals. Using in situ transmission electron microscopy nanomechanical testing, we demonstrate that highly pressurized helium nanobubbles can not only increase the strength by serving as dislocation obstacles but also enhance the strain hardening capacity and accommodate considerable plasticity via facilitating the multiplication and interaction of interwoven stacking faults. Through atomistic simulations, we reveal that high helium pressures contribute to reducing the nucleation energy of partial dislocations at the nanobubbles surface, which enhances dislocation nucleation rates and offers sustainable stacking fault sources for retaining ductility. Our results provide a novel design strategy for tuning deformation mechanisms of HEAs via introducing highly pressurized helium nanobubbles, which may open up avenues towards the facile tailoring of mechanical responses in micro/nanoscale HEA components. Graphical Abstract: Image, graphical abstract